Peranan Kemasan Dalam Transportasi Produk Bahan Berbahaya Dan Beracun - Budi Utami (Jurnal Kimia dan Kemasan, 1998)
The function of packaging especially for dangerous goods essentially to contain the product protecting it from the environment, and also protecting the environment from being polluted by the content. Labelling will provide the information about the content and handling system.The requirement for dangerous goods transport packaging refers to the UN Standard which include drops test, stacking test, leakproofness, and internal pressure.The test condition de pens on the type of packaging, the material, and the content.